PENGARUH METODIK KHUSUS MENGAJAR LOMPAT TINGGI TERHADAP HASIL LOMPAT TINGGI GAYA FLOP MAHASISWAANGKATAN PRODI PENDIDIKAN KEPELATIHAN OLAHRAGA TAHUN 2015 - Rudy Kurnianto; Ramadi '; Ni putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Athletics is one of the oldest sports, which has been done by man since ancient times until today, even since human existence on this earth's atelic already exists. One branch has altetik jumped. The purpose of this research was to determine how much high-tech methodological education practice influenced the results of high jump flop style Sports Coaching Education students Prodi Year 2015. The research design uses one-party pretest post test design. This type of research experiment performed in the form of Pree test and post-test performed. The population in this study is the student of the Department of Education Coaching in 2015 enrolled in the academic year 2015/2016 as much as 40 students. Samples to be treated and exercised by researchers only 14 people who are Prodi Students Sport Coaching Education Year 2015. The sample forms because the number of these students may not reach the 2nd semester exam grades in high jump. Data analysis techniques in this study are the formula t-test. Based on the t-test analysis, it showed that sebesar7,3979 T and T table of 1,761. Means the table, which means that Ho refused and accepted H1. Thus, it can be concluded that there is a significant influence to exert special methodic education high jump (X) with the high jump flop style (Y) at a sports coaching student education students University of Riau in alpha level of 0.05 or with a reliability of 95%Keywords: Be Special Methodical, High Jump.